Analytical validation of the 7-gene biosignature for prediction of recurrence risk and radiation therapy benefit for breast ductal carcinoma in situ - Dabbs, David; Mittal, Karuna; Heineman, Scott; Whitworth, Pat; Shah, Chirag; Savala, Jess; Shivers, Steven C.; Bremer, Troy (Frontiers in Oncology, 2023)
Purpose: Ductal carcinoma in situ (DCIS), is a noninvasive breast cancer, representing 20-25% of breast cancer diagnoses in the USA. Current treatment options for DCIS include mastectomy or breast-conserving surgery (BCS) with or without radiation therapy (RT), but optimal risk-adjusted treatment selection remains a challenge. Findings from past and recent clinical trials have failed to identify a ‘low risk’ group of patients who do not benefit significantly from RT after BCS. To address this unmet need, a DCIS biosignature, DCISionRT (PreludeDx, Laguna Hills, CA), was developed and validated in multiple cohorts. In this study, we present results from analytical validity, performance assessment, and clinical performance for the DCISionRT test comprised of multianalyte assays with algorithmic analysis. Methods: The analytical validation of each molecular assay was performed based on the Clinical and Laboratory Standards Institute (CLSI) guidelines Quality Assurance for Design Control and Implementation of Immunohistochemistry Assays and the College of American Pathologists/American Society of Clinical Oncology (CAP/ASCO) recommendations for analytic validation of immunohistochemical assays. Results: The analytic validation showed that the molecular assays that are part of our multianalyte assays have high sensitivity, specificity, and accuracy/reproducibility (≥95%). The analytic precision of the molecular assays under controlled non-standard conditions had a total standard deviation of 6.6 (100-point scale), where the analytic variables (Lot, Machine, Run) each contributed <1% of the total variance. Additionally, the precision in the DCISionRT test result (DS) had a 95%CI <0.2 DS units under controlled non-standard conditions (Day, Lot, and Machine) for molecular assays over a wide range of clinicopathologic factor values. Clinical validation showed that the test identified 37% of patients in a low-risk group with a 10-year invasive IBR rate of less than 5% and an absolute risk reduction (ARR) from RT of 1% (number needed to treat, NNT = 100), while remaining patients with higher DS scores (elevated-risk) had an ARR for RT of 9% (NNT=11). Conclusion: The analytical performance of the PreludeDx DCISionRT molecular assays was high in representative FFPE breast tumor specimens. The DCISionRT test has been analytically and clinically validated.